LEGAL STATUS OF A TEACHER IN UZBEKISTAN - Suvankulov Jamshid Abdulahadovich (Web of Journals Publishing, 2024)
This article analyzes the legal status of teachers in Uzbekistan. Some proposals were also made to further strengthen the rights of the teacher.
Keywords: Teacher’s rights, pedagogical activity, responsibility